Employee Task Allocation System - A.Nalini (International Journal of Engineering and Management Research, 2019)
To maintain track of the data about the employees in every given business, a distributed application server called the employee job allocation system was developed. Both the technology utilised to produce work status and information about the employees' personal details are kept on file. Anyone can utilise it because it's straightforward to understand, even people who aren't familiar with a basic workers task system. It is easy to use and only gives the user a limited number of alternatives while instructing him to do tasks step by step.